Kajian Pemukiman Majapahit di Trowulan Melalui Peninggalan Arkeologi - Annajmia Sofi Camelia Prahasinta; Camelia Prahasinta (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2022)
Majapahit Kingdom is one of the great kingdoms in the classical Hindu-Buddhist period that once stood in the archipelago. The founder of Majapahit Kingdom was Raden Wijaya. Majapahit in the XII - XV century AD was a superpower and superpower in southeast Asia. Trowulan area is the area that is thought to be the former capital of Majapahit kingdom. To track the boundaries of the former majapahit city can be done through the Trowulan site area located in mojokerto, East Java.This article will discuss about majapahit settlement in Trowulan and surrounding areas and written using historical methods consisting of topic selection, heuristics, criticism, interpretation and historiography.